Youth in extension and advisory services: Rwanda - Franzel, S.; Kinyua, H.; Rucibigango, M.; Davis, Kristin E.; Makh, S. (United States Agency for International Development, 2019)
Approximately 88 percent of the world’s 1.2 billion youth (ages 15-24 as defined by the UN) live in developing countries. By 2050, the global population of youth is projected to rise to 1.8 billion, with 35 percent of that estimated to live on the African continent. This presents a challenge to many developing countries given the need to create economic opportunities for this growing segment of the population. According to the World Bank, even if countries had suitable conditions for growth and economic transformation, the job market in developing countries could not absorb the growing number of young people projected to become eligible for jobs. In addition to the youth bulge, meeting the growing global demand for food and nutrition also presents a challenge, with some estimates citing a need to increase food availability by 70-100 percent. At the same time, factors such as an increasingly globalized and connected world, higher global incomes, urbanization and widespread access to digital tools are creating new opportunities in agri-food systems for youth and other rural actors. Tapping into the potential of youth and creating opportunities for them in agriculture, including in extension and advisory services (EAS), will be key to meeting global food and nutrition needs as well as achieving the Sustainable Development Goals (SDGs) and Feed the Future’s Food Secure 2030 vision. Rural extension and advisory services are defined as all the different activities that provide the information and services needed by farmers and other players in the agri-food system and rural development to develop and build their technical, organizational and management capacities, so they can improve their quality of life and well-being (Christoplos, 2010).